2001
DOI: 10.1037/1076-8998.6.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Incivility in the workplace: Incidence and impact.

Abstract: This study extends the literature on interpersonal mistreatment in the workplace by examining the incidence, targets, instigators, and impact of incivility (e.g., disrespect, condescension, degradation). Data were collected from 1,180 public-sector employees, 71% of whom reported some experience of workplace incivility in the previous 5 years. As many as one third of the most powerful individuals within the organization instigated these uncivil acts. Although women endured greater frequencies of incivility tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

85
2,098
6
45

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 1,536 publications
(2,234 citation statements)
references
References 76 publications
85
2,098
6
45
Order By: Relevance
“…In the Uncivil condition, one actor undermined the ideas of the other through body language and tone of voice consistent with several items on the Workplace Incivility Scale (Cortina et al, 2001). In the Civil condition, the actors stated and responded to the ideas in a neutral way.…”
Section: Study 2 Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the Uncivil condition, one actor undermined the ideas of the other through body language and tone of voice consistent with several items on the Workplace Incivility Scale (Cortina et al, 2001). In the Civil condition, the actors stated and responded to the ideas in a neutral way.…”
Section: Study 2 Methodsmentioning
confidence: 67%
“…Observers who react positively toward a target may buffer the negative effects of incivility on targets (e.g., Cortina et al, 2001), whereas those who react negatively, or even those who do nothing, may exacerbate these negative outcomes (see for example Duffy, Ganster, & Pagon, 2002). Given the prevalence and gravity of incivility at work, understanding observer reactions toward targets is critical.…”
Section: Deontic Responses To Witnessed Incivilitymentioning
confidence: 99%
“…Although scales in the questionnaire were designed to address relatively discrete behaviors, perhaps participants reported the same harassment experiences on both the Sexual Experiences Questionnaire-Revised and the Workplace Incivility Scale. To avoid this possibility, all analyses in the present article included only a subset of the seven original Workplace Incivility Scale items (Cortina et al, 2001), removing the ones that seemed most vulnerable to double counting (e.g., "addressed you in unprofessional terms"). It was thus unlikely that double counting would explain the correlations among the different types of mistreatment.…”
Section: Methodsological Issuesmentioning
confidence: 99%
“…Supporting these arguments, Pearson and colleagues (Pearson, Andersson, & Porath, 2000;Pearson, Andersson, & Wegner, 2001) found that targets of incivility often experienced negative affective and cognitive reactions at work (e.g., worrying about future interactions with the instigator), and many eventually quit their jobs. Initial data from Cortina et al (2001Cortina et al ( , 2002 also showed direct links between incivility experiences and lower job satisfaction. Moreover, a number of studies have found that dissatisfaction with the job predicts various job withdrawal behaviors, including turnover and retirement (e.g., Hanisch & Hulin, 1990;1991).…”
Section: Work Outcomesmentioning
confidence: 98%